2000
DOI: 10.1097/00005344-200006000-00005
|View full text |Cite
|
Sign up to set email alerts
|

SM-20550, a New Na+/H+ Exchange Inhibitor and Its Cardioprotective Effect in Ischemic/Reperfused Isolated Rat Hearts by Preventing Ca2+-Overload

Abstract: We investigated the effect of a newly synthesized compound, SM-20550 [N-(aminoiminomethyl)-1,4-dimethyl-1H-indole-2-carboxamide methanesulfonic acid] on Na+/H+ or Na+/Ca2+ exchange activity in rat cardiomyocytes, and on radioligand binding with several channels or receptors in membrane preparations, and ischemia/reperfusion injury in isolated perfused rat hearts. In myocytes, SM-20550 concentration-dependently inhibited the recovery from acidosis induced by an NH4Cl prepulse in HCO3(-)-free solution. Its IC50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…6. In this series of experiments, 7 μ m ruthenium red, 0.1 μ m cyclosporin A and 10 μ m SM20550 (IC 50 = 10 n m ; Yamamoto et al 2000) were added to the bath solution to suppress the mitochondrial Ca 2+ uniporter, PTP, and the mitochondrial Na + –H + exchange, respectively. Applying 600 n m Ca 2+ c did not significantly increase the Rhod‐2 fluorescence, but membrane depolarization by 1 μ m FCCP and 2 μ m oligomycin (FCCP + Olig, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6. In this series of experiments, 7 μ m ruthenium red, 0.1 μ m cyclosporin A and 10 μ m SM20550 (IC 50 = 10 n m ; Yamamoto et al 2000) were added to the bath solution to suppress the mitochondrial Ca 2+ uniporter, PTP, and the mitochondrial Na + –H + exchange, respectively. Applying 600 n m Ca 2+ c did not significantly increase the Rhod‐2 fluorescence, but membrane depolarization by 1 μ m FCCP and 2 μ m oligomycin (FCCP + Olig, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These inhibitors, however, are known to affect other sarcolemmal proteins, including NCX (11). Newer, more specific NHE-1 inhibitors have been shown to reduce myocardial damage after I/R injury that is characterized by an improvement in the postischemic recovery of left ventricular developed pressure, decreases in creatine phosphate release, and a reduction in tissue Na ϩ and Ca 2ϩ content (5,16,24,40).…”
Section: Discussionmentioning
confidence: 99%
“…In myocardial ischemia and reperfusion injury, the Na + /H + exchanger has been shown to be involved in arrhythmia, stunning and necrosis in several models, using inhibitors of the Na + /H + exchanger such as ethylisopropyl-amiloride [1], HOE694 [3,6], HOE642 [2,5], EMD85131 [4], and SM-20550 [7,8,10]. Many studies have revealed the effectiveness of inhibitors of the Na + / H + exchanger in attenuating myocardial ischemia and reperfusion injury in rabbit, porcine and canine models with short reperfusion period; however, the present study is the first demonstration of the effect of as inhibitor of Na + /H + exchanger, SM-20550, on survival rate after a long-term reperfusion period in any species.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated that a novel potent Na + /H + exchange inhibitor, SM-20550, which has IC 50 of 10 nmol/l for Na + /H + exchange activity in rat cardiomyocytes and little effect on several channels or receptors [7], has a cardioprotective effect in a rat isolated perfusion model [7], and reduces myocardial necrosis in a rabbit myocardial infarction model [8]. Many studies have shown the involvement of the Na + /H + exchanger in myocardial necrosis in rabbit [1,2], porcine [3] and canine [4] models of cardiac ischemia with short reperfusion period; however, there has been no demonstration of the effect of Na + /H + exchange inhibitors on prognosis after myocardial infarction after a long-term reperfusion period.…”
Section: Introductionmentioning
confidence: 99%